Micro-nutrient related malnutrition and obesity in a university undergraduate population and implications for non-communicable diseases - Foluke A Olatona; Sunday A Aderibigbe; Eyitope O Amu; Oluseye O Onabanjo; Kelechi E Nnoaham (Journal of Global Health Reports)
# Background Micronutrient deficiency and obesity are increasing globally. This study determined the prevalence of micronutrient-related malnutrition, patterns of obesity using different methods of assessment, and the predictors of obesity among the university undergraduate population in Lagos State, Nigeria.